DESIGN OF FRICTION COEFFICIENT TEST EQUIPMENT FOR RAILWAY COMPOSITE BRAKE BLOCK - Putri Ariesta, Chyka
Railway is a crucial mode of public transportation that plays a significant role in supporting the nation's economy. Brake blocks are one of the most critical components of a railway braking system. The use of composite brake blocks in railway systems has been growing rapidly, replacing traditional metal-based brake blocks. The National Standardization Body (Badan Standardisasi Nasional or BSN) is currently developing quality standards (SNI) for composite brake blocks. To ensure their compliance with these standards, it is essential to conduct testing of the material properties of composite brake blocks, including their coefficient of friction. However, there is currently no laboratory in Indonesia equipped with a testing apparatus to determine the coefficient of friction for composite railway brake blocks. Therefore, this undergraduate thesis aims to design a testing apparatus for measuring the coefficient of friction of composite railway brake blocks. The process of developing this undergraduate thesis project begins with the collection of information about existing coefficient of friction testing equipment. Subsequently, Design Requirements and Objectives (DR&O) are established. Following this, conceptual designs are developed to formulate suitable design alternatives, which are then followed by the 3D modeling of the proposed testing apparatus. The next stage involves calculating the maximum stress on critical components using Ansys software, with theoretical calculations serving as validation steps. Based on the calculations and an analysis of the power requirements for driving the testing apparatus, it is determined that a motor with a power rating of 334.13 kW is needed. The required braking force is 5 kN, resulting in a hydraulic cylinder thrust requirement of 25 kN. The chosen power transmission method is the use of V-belts, with a total of 8 belts, each with a power rating of 58.06 kW.